2018
DOI: 10.1590/s1679-45082018ao4224
|View full text |Cite
|
Sign up to set email alerts
|

Oral colonization by Candida species in HIV-positive patients: association and antifungal susceptibility study

Abstract: Objective To investigate antifungal susceptibility and factors associated with oral colonization by Candida species in HIV-positive patients.Methods A prospective study based on convenience sampling of subjects recruited from a pool of confirmed HIV-positive individuals seen at a specialty outpatient service in Rondonópolis, Mato Grosso, Brazil). Oral swabs were collected from 197 patients. Candida species were identified by standard microbiological techniques (phenotypic and molecular methods). Antifungal sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 33 publications
6
35
2
7
Order By: Relevance
“…In other study, Takahashi et al (2015) revealed increasing age (p = 0.007; Adjusted OR = 1.02; 95% CI: 1.00-1.03) was significantly associated with OC. 12 Goulart et al (2018) found that age was the risk factor for oral colonization bay Candida spp; colonization was associated to participants aged 45 to 59 years (p= 0.0273; PR: 1.90; 95% CI: 1.57-6.31) and 60 years or more (p=0.0273; PR: 4.43; 95% CI: 1.57-34.18), colonization risks increased with age. 22 Owotade et al (2013) reported that age was the risk factor for oral Candidiasis (P=0.034; OR= 0.95; 95% CI: 0.90-0.99).…”
Section: Discussionmentioning
confidence: 98%
“…In other study, Takahashi et al (2015) revealed increasing age (p = 0.007; Adjusted OR = 1.02; 95% CI: 1.00-1.03) was significantly associated with OC. 12 Goulart et al (2018) found that age was the risk factor for oral colonization bay Candida spp; colonization was associated to participants aged 45 to 59 years (p= 0.0273; PR: 1.90; 95% CI: 1.57-6.31) and 60 years or more (p=0.0273; PR: 4.43; 95% CI: 1.57-34.18), colonization risks increased with age. 22 Owotade et al (2013) reported that age was the risk factor for oral Candidiasis (P=0.034; OR= 0.95; 95% CI: 0.90-0.99).…”
Section: Discussionmentioning
confidence: 98%
“…This prevalence was similar to the values observed in people undergoing autologous bone marrow transplantation (40.7%) and asymptomatic PLHIV (51.3% and 52.5%), but lower than the values found in hospitalized HIV patients (50.4%, 53.5%, 73.3%, 73.4%, 80%, and 83%). [6,[22][23][24][25][26][27][28] It is important to consider the period and location of these studies (Brazil, China, Nigeria, Turkey) once the incidence of fungal infections has increased in developing countries due to the use of ART and new diagnostic methods. [29] Moreover, the participants in this study come from the outpatient clinics and not from the hospitals; hence, these participants may present basic pathologies that aggravate their clinical status.…”
Section: Discussionmentioning
confidence: 99%
“…Oral candidiasis is one of the first clinical signs of AIDS found in 50% to 95% of HIV/AIDS patients. The condition is mostly caused by Candida albicans, which number is around 2-69.1% found in adult's oral cavity 1,2 . Candida albicans is not the only species causing candidiasis, but also other species including Candida glabrata, Candida krusei, Candida tropicalis, Candida parapsilosis and Candida dubliniensis.…”
Section: Introductionmentioning
confidence: 99%
“…Early treatment of oral candidiasis, according to WHO, includes administration of topical antifungal agents, such as nystatin, amphotericin B, miconazole, and clotrimazole. Those agents can be given in oral candidiasis case without complication 2,5 .…”
Section: Introductionmentioning
confidence: 99%